33.0k views
5 votes
Could you help me solve this equation? (Not from a graded assignment)

Could you help me solve this equation? (Not from a graded assignment)-example-1

1 Answer

3 votes

Answer:

The question is given below as


(x^(-3))^2.x^8

Step 1:

Use the exponent formula below


(x^m)^n=x^(m* n)=x^(mn)
(x^(-3))^2=x^(-3*2)=x^(-6)

Apply the rule below


\begin{gathered} x^a* x^b=x^(a+b) \\ x^(-6)* x^8=x^(-6+8)=x^2 \\ =x^2 \end{gathered}

Hence,

The final answer is


\Rightarrow x^2

The FIRST OPTION IS THE RIGHT ANSWER

User SlimJim
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.